Donor selection for blood safety: is it still necessary?. (28th July 2014) - Lin, C. K.; Leung, J. N. S.; So, B. K. L.; Lee, C. K.
Abstract : The strive for zero risk blood transfusion is still an ongoing challenge in many countries despite the application of new laboratory blood testing technologies. Predonation blood donor screening has been playing a crucial role in minimizing the collection of blood from 'unsafe' donors. This article aims at reviewing the various approaches to ensure blood safety and the factors that need to be considered in drawing up effective strategies that suit the local need.